Molecular and Biochemical Characterization of Salt-Tolerant Trehalose-6-Phosphate Hydrolases Identified by Screening and Sequencing Salt-Tolerant Clones From the Metagenomic Library of the Gastrointestinal Tract - Yang, Yanxia; Yang, Yunjuan; Fan, Qin; Huang, Zunxi; Li, Junjun; Wu, Qian; Tang, Xianghua; Ding, Junmei; Han, Nanyu; Xu, Bo (Frontiers in Microbiology, 2020)
Exploring and utilizing enzymatic and genetic resources for salt tolerant bacteria is of great significance in the study of biological adaptation to extreme environments. The presence of new salt tolerance genes in the microbial metagenomic library of the gastrointestinal tract has been confirmed through metagenomic technology. This paper aimed to identify and characterize enzymes that confer salt tolerance in the gastrointestinal tract microbe. By screening the fecal metagenomic library, 48 salt tolerance clones were detected, of which 10 salt tolerance clones exhibited stronger tolerance to 7% NaCl and stability in different concentrations of NaCl (5%−9%). High-throughput sequencing and biological information analysis showed that 91 potential genes encoded proteins that were widely involved in salt tolerance. Furthermore, two trehalose-6-phosphate hydrolase genes, namely, tre_P2 and tre_P3, were successfully cloned and expressed in Escherichia coli BL21 (DE3). By virtue of the substrate of p-nitrophenyl-α-D-glucopyranoside (pNPG), the two enzymes can act optimally at PH 7.5 and 30°C. Steady-state kinetics with pNPG showed that the Km and Kcat values were 15.63 mM and 10.04 s−1 for TRE_P2 and 12.51 mM and 10.71 s−1 for TRE_P3, respectively. Characterization of enzymatic properties demonstrated that TRE_P2 and TRE_P3 were salt tolerant. The enzymatic activity increased with increasing NaCl concentration, and the maximum activities of TRE_P2 and TRE_P3 were obtained at 4 and 3 M NaCl, respectively. The activities of TRE_P2 increased by approximately 43-fold even after 24 h of incubation with 5 M NaCl. This study is the first to report the identification as well as molecular and biochemical characterization of salt-tolerant trehalose-6-phosphate hydrolase from the metagenomic library of the gastrointestinal tract. Results indicate the existence of numerous salt tolerance genes and enzymes in gastrointestinal microbes and provide new insights into the salt tolerance mechanisms in the gastrointestinal environment.